2018
DOI: 10.1093/jas/sky021
|View full text |Cite
|
Sign up to set email alerts
|

Energy costs of feeding excess protein from corn-based by-products to finishing cattle

Abstract: The increased use of by-products in finishing diets for cattle leads to diets that contain greater concentrations of crude protein (CP) and metabolizable protein (MP) than required. The hypothesis was that excess dietary CP and MP would increase maintenance energy requirements because of the energy costs of removing excess N as urea in urine. To evaluate the potential efficiency lost, two experiments were performed to determine the effects of feeding excess CP and MP to calves fed a finishing diet at 1 × maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
4
20
1
Order By: Relevance
“…In many cases, however, consumers may be constrained to diets that are richer in protein relative to carbohydrate and lipid than is optimal (Rothman et al, 2011;Jensen et al, 2014;Nyffeler et al, 2016;Remonti et al, 2016;Wiggins and Wilder, 2018). Animals must then use protein as a source of energy, potentially leading to the onset of toxicity via deamination and release of ammonia and incurring various energetic and other costs associated with metabolic transformations, synthesis of reduced forms of N and excretion (Bender, 2012;Piper et al, 2017;Reed et al, 2017;Jennings et al, 2018). High dietary nutrient content can thus be "too much of a good thing" (Boersma and Elser, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, however, consumers may be constrained to diets that are richer in protein relative to carbohydrate and lipid than is optimal (Rothman et al, 2011;Jensen et al, 2014;Nyffeler et al, 2016;Remonti et al, 2016;Wiggins and Wilder, 2018). Animals must then use protein as a source of energy, potentially leading to the onset of toxicity via deamination and release of ammonia and incurring various energetic and other costs associated with metabolic transformations, synthesis of reduced forms of N and excretion (Bender, 2012;Piper et al, 2017;Reed et al, 2017;Jennings et al, 2018). High dietary nutrient content can thus be "too much of a good thing" (Boersma and Elser, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Zinn et al (1997) concluded that N excretion through urine in beef steers required 7.9 Kcal/g of N and Tyrrell et al (1970) determined that 10.8 Kcal of digestible energy were required per g of excess urinary N excretion in dairy cows. Jennings et al (2018) noted that maintenance energy requirements of steers increased approximately 4 to 6% when dietary CP concentrations were increased from 13.5 to 18% using a corn-based protein (corn gluten meal) source.…”
Section: Methodsmentioning
confidence: 99%
“…In the body, excess N is converted to urea in the liver and then excreted in the urine. Jennings et al (2018) conducted two experiments to determine the effects of feeding excess CP and MP (using corn gluten feed and corn gluten meal) on the maintenance-energy requirements of steers fed a finishing diet at 1 or 2 • maintenance-energy intake. Maintenance-energy requirements, estimated from linear and quadratic regression of energy retention on metabolisableenergy intake, were 4-6% greater for steers overfed CP (19.5% CP with 14.14% MP) than for control steers receiving 13.8% CP with 9.63% MP.…”
Section: Animal Costs Of Excess Proteinmentioning
confidence: 99%
“…Maintenance-energy requirements, estimated from linear and quadratic regression of energy retention on metabolisableenergy intake, were 4-6% greater for steers overfed CP (19.5% CP with 14.14% MP) than for control steers receiving 13.8% CP with 9.63% MP. Jennings et al (2018) suggested that feeding excess CP and MP from a protein source that is high in RDP and low in protein quality will increase maintenance-energy requirements of finishing steers.…”
Section: Animal Costs Of Excess Proteinmentioning
confidence: 99%
See 1 more Smart Citation